2001 Conference Proceedings of the 23rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2001.1017423
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transdermal ballistic delivery of micro-particles into human and porcine skin

Abstract: Abstract-This paper describes a comparative investigation into the impact penetration characteristics of DNA-coated gold micro-particles into human and porcine skin. This work is aimed at establishing the link between the particle parameters required in delivering particles to the epidermis of pigs and humans.The particles are delivered to the skin using the PowderJect concept: a method that accelerates vaccines and drugs in microparticle form to velocities sufficient to penetrate the skin and achieve a therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Various studies have adopted that the drag force acting on the microparticles is split into a yield force (F y ), a frictional resistive force (F f ) and a resistive inertial force of target material (F i ) (Dehn, 1987;Kendall et al, 2001;Mitchell et al, 2003;Liu, 2007;. Thus, Equation (7) is written as:…”
Section: Deceleration Stagementioning
confidence: 99%
“…Various studies have adopted that the drag force acting on the microparticles is split into a yield force (F y ), a frictional resistive force (F f ) and a resistive inertial force of target material (F i ) (Dehn, 1987;Kendall et al, 2001;Mitchell et al, 2003;Liu, 2007;. Thus, Equation (7) is written as:…”
Section: Deceleration Stagementioning
confidence: 99%
“…For the penetration stage, various studies have separated the resistance force on the micro-particle into a yield force (F y ), frictional resistive force (F f ) and resistive inertial force of the target material (F i ; Dehn, 1987;Kendall et al, 2001;Mitchell et al, 2003;Liu, 2007;. The force balance equation is shown below:…”
Section: Modeling Micro-particle Delivery In Skinmentioning
confidence: 99%
“…For example, have modeled the delivery of golden particle of diameters 1.8 and 5 mm using 3 MPa pressure and have shown that penetration depths of 95 and 135 mm can be achieved for particle of diameters 1.8 and 5 mm, respectively. Kendall et al (2001) have analyzed the golden particle penetration by using Equation (2) for particle penetration in human and porcine skins. In addition, predictions from the theoretical model have been shown to agree well with the experimental results by Kendall et al (2001).…”
Section: Modeling Micro-particle Delivery In Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, histological studies of the skin are limited to excised animal and human samples-live tissue cannot be studied in-vivo 16 . The histology process is also labor intensive: slides are prepared from across the footprint, imaged and analyzed individually using a microscope.…”
Section: Introductionmentioning
confidence: 99%